Serum bile acids as marker for acute decompensation and acute‐on‐chronic liver failure in patients with non‐cholestatic cirrhosis. (4th August 2016) - Horvatits, Thomas; Drolz, Andreas; Roedl, Kevin; Rutter, Karoline; Ferlitsch, Arnulf; Fauler, Günter; Trauner, Michael; Fuhrmann, Valentin
Abstract: Background & Aims: Retention of bile acids (BAs) plays a central role in hepatic damage and disturbed BA signalling in liver disease. However, there is lack of data regarding the association of BAs with clinical complications, acute decompensation (AD) and acute‐on‐chronic liver failure (ACLF). Thus, we aimed to evaluate the impact of circulating serum BAs for complications in patients with cirrhosis. Methods: One hundred and forty‐three patients with cirrhosis were included in this prospective cohort‐type observational study. Total serum BAs and individual BA composition were assessed in all patients on admission via high‐performance liquid chromatography. Clinical complications with respect to AD, ACLF and 1‐year transplant‐free survival were recorded. Results: Total BAs and individual serum BAs were significantly higher in patients with bacterial infection, AD and ACLF ( P <.001) and correlated significantly with model of end‐stage liver disease (MELD) and hepatic venous pressure gradient ( P <.001). Total BAs predicted new onset of AD or ACLF during follow‐up (OR 1.025, 95% CI: 1.012–1.038, P <.001). Best cut‐off predicting new onset of AD/ACLF and survival during course of time was total BAs ≥36.9 μmol/L. Conclusions: Serum total and individual BAs are associated with AD and ACLF in patients with cirrhosis. Assessment of total BAs could serve as additional marker for risk stratification in cirrhotic patients with respect to new onset of AD and ACLF.